Interleukin-1 in malnutrition. Issue 2 (February 1986) - Bhaskaram, P; Sivakumar, B
Abstract : The effect of malnutrition on the in vitro production of interleukin-1 by lipopolysaccharide stimulated circulating monocytes has been investigated in children suffering from kwashiorkor and marasmus. The interleukin-1 activity was significantly lower in children with severe malnutrition. Furthermore, macrophages from children with kwashiorkor produced factors that suppressed mouse thymocyte proliferation. These observations show a significant impairment of macrophage function and provide a mechanism for the suppression of cellular immunity in malnutrition.